PENGARUH KERAGAMAN PRODUK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA MINIMARKET RUSDI WIDORO PAYUNG - Randika Fandiyanto; Fajar Wahyu Prianto (Relawan Jurnal Indonesia, 2021)
This study aims (1) to determine the effect of product diversity, price and location partially on purchasing decisions (2) to determine the effect of product diversity, price and location simultaneously on purchasing decisions (3) to find out which among the diversity of products, prices and locations which has a dominant influence on purchasing decisions. The method used in this research is quantitative method. The results of multiple linear regression analysis are Y = 2,888E-16 + 0,186 X1 + 0,475 X2 + 0,184 X3 + 0,088 e. Partially, product diversity has a significant positive effect on purchasing decisions with a value of 2,094> 1,985, price has a significant positive effect on purchasing decisions with a value of 5,317> 1,985, location has a significant positive effect on purchasing decisions with a value of 2,065> 1,985. Simultaneously the diversity of products, prices, and location together have a significant positive effect on purchasing decisions with a value of 11,172> 2.70. The dominant influential variable in this study is the price variable with a value of 5,317.